Dangerous associations: Racializing urban communities and the influence of one critical service-learning course to disrupt racist ideological habits. (2nd January 2022) - Stockton, T. J.
ABSTRACT: This study examined pre-service teachers' initial perceptions of urban communities and schools. Furthermore, it explored whether engaging in critical service-learning coursework incorporating an anti-racist curriculum disrupted the mechanisms that perpetuate racist ideological habits and associations. The narrative analysis deconstructed 12 participants' reflective essays using a critical race theoretical lens. The overall findings revealed that the participants experience urban communities through racist associations and ideologies promoting white supremacist thinking. The critical service-learning course did influence the perceptions of the participants. However, findings suggest that a single critical service-learning course is insufficient to prepare pre-service teachers with the anti-racist pedagogies necessary for disrupting the ideological habits they bring to the classroom. Therefore, this study concluded that teacher education programs should infuse anti-racist development as an ongoing and progressive aspect of their program.